Pterostilbene in Combination With Mitochondrial Cofactors Improve Mitochondrial Function in Cellular Models of Mitochondrial Diseases - Suárez-Rivero, Juan M.; Pastor-Maldonado, Carmen J.; Romero-González, Ana; Gómez-Fernandez, David; Povea-Cabello, Suleva; Álvarez-Córdoba, Mónica; Villalón-García, Irene; Talaverón-Rey, Marta; Suárez-Carrillo, Alejandra; Munuera-Cabeza, Manuel; Sánchez-Alcázar, José A. (Frontiers in Pharmacology, 2022)
Mitochondrial diseases are genetic disorders caused by mutations in genes in the nuclear DNA (nDNA) and mitochondrial DNA (mtDNA) that encode mitochondrial structural or functional proteins. Although considered “rare” due to their low incidence, such diseases affect thousands of patients’ lives worldwide. Despite intensive research efforts, most mitochondrial diseases are still incurable. Recent studies have proposed the modulation of cellular compensatory pathways such as mitophagy, AMP-activated protein kinase (AMPK) activation or the mitochondrial unfolded protein response (UPRmt) as novel therapeutic approaches for the treatment of these pathologies. UPRmt is an intracellular compensatory pathway that signals mitochondrial stress to the nucleus for the activation of mitochondrial proteostasis mechanisms including chaperones, proteases and antioxidants. In this work a potentially beneficial molecule, pterostilbene (a resveratrol analogue), was identified as mitochondrial booster in drug screenings. The positive effects of pterostilbene were significantly increased in combination with a mitochondrial cocktail (CoC3) consisting of: pterostilbene, nicotinamide, riboflavin, thiamine, biotin, lipoic acid and L-carnitine. CoC3 increases sirtuins’ activity and UPRmt activation, thus improving pathological alterations in mutant fibroblasts and induced neurons.